Pemberdayaan Usaha Mikro Kecil dan Menengah Untuk Meningkkatkan Kinerja Penjualan Pada Usaha Jahe Emprit - udayana Ida Bagus; Dika Prawita; Misbach Fuady; Budi Setiawan; Abdul Rokhim (JCSE: Journal of Community Service and Empowerment, 2025)
The main problems faced by the partner, “Sekar Socan” ginger (jahe emprit) business, include unstable production processes due to high raw material costs and limited marketing that relies primarily on offline channels. This community service program aims to revitalize and develop the business to compete in the national market while promoting the consumption of ginger-based beverages among the Indonesian community. The methods applied include the Economic Order Quantity (EOQ) approach to improve raw material inventory management and online marketing optimization through the development of a modern MSME website and the utilization of social media platforms such as WhatsApp and Instagram. The results indicate an improvement in the entrepreneurs’ understanding of inventory control, digital marketing, product packaging innovation, and financial literacy. The implications of this program include enhanced business capacity, expanded market reach, stronger product positioning, and improved sales performance.